A Critical Review on the Understanding and Management of Vatarakta - Uniyal, Divya; Shukla, Gyanendra Datta; Arora, Vipin (International Research Journal of Ayurveda & Yoga, 2022)
Vata Dosha is considered as the prime Dosha as it is responsible for all the movements in the body. The disease Vatarakta holds a special place in the Ayurvedic literature due to its high prevalence in the society. . The vitiated Rakta Dhatu obstructs the pathway of enraged Vayu which in turn vitiates the Rakta further giving rise to the disease Vatarakta. The disease can be correlated with Gouty Arthritis due to similarity in the clinical presentation. Vatarakta is a progressive disorder, where the disease is initially limited to the superficial Dhatu leading to Uttana Vatarakta but later on involves the deep Dhatu giving rise to Gambhira Vatarakta. The allopathic treatment give rise to many side effects and adverse reactions. Ayurveda can provide a a good holistic treatment option. The treatment described in Ayurveda not only focuses on drugs but also on the life style modification. Keeping all the points in mind, the disorder has been considered for the study to find an effective and safe cure for the disease. The present study gives a sight of critical review of the disease Vatarakra and the aim of the review is to review and highlight the effectiveness of different Ayurvedic treatment modalities in patients with Vatarakta.